The Urgency of Fatwa in The Law of Sharia Economics in Indonesia - Elsy Renie (JURIS (Jurnal Ilmiah Syariah), 2021)
Fatwas of the National Sharia Council-Indonesian Ulama Council (DSN-MUI), in the field of sharia economics, has filled the legal vacuum related to the economic activities of the people. The increased of activity in the Mu'amalah area which is so fast requires a responsive fatwa. It can be seen from the rapid development of financial products for sharia financial institutions today. The legal strength of a fatwa is non-binding because it is not included in the constitution hierarchy in Indonesia which has caused debate for some people. But, several DSN-MUI fatwa have been transformed into part of national law, such as constitution No. 21 of 2008 concerning Banking, and some of which have also been absorbed into Bank Indonesia regulations, Syari'ah Financial Services Authority Regulation (OJK). This paper tries to analyze the role of fatwas in filling the legal vacuum in the development of the shari'ah economy in Indonesia and how the fatwas of the DSN-MUI can be transformed into national law. The author concludes that the role of DSN-MUI as the only institution that issued a fatwa related to the activities of shari'ah financial institutions in Indonesia is very important in the area of national legal politics.